(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Trauma is the leading cause of disability in the first four decades of life and third most common cause of death. Spinal trauma poses considerable threats to survival and quality of life. Objective: Aims of this study is to assess the demographics, mode of trauma, hospital stay, complications, neurological improvement and mortality. Methods: Retrospective Cross sectional analysis of the records of spinal injury patients admitted in the Spine Unit of Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital from October 2003 to December 2013 was carried out. The demographics, mode of trauma, involved vertebral level, co-morbid factors; neurological status and its improvement by American Spinal Injury Association (ASIA) Score, duration of hospital stay and complications during hospital stay was assessed. Results were analyzed by SPSS. Results: Out of 1288 patients admitted, 192(14.90%) patients(range, 8-72 years) sustained spinal injuries and most (63.02%)of them were young (range, 21-40 years). Male to female ratio was 5:1. Cervical spine was most commonly ( 44.66%) affected followed by lumbar (35 .41 % ), thoracic (13 .54% ), thoraco-lumbar (06.25%) and Cervico-thoracic (03.13%) region. Fracture through intervertebral disc was most common in cervical spine. Among the common causes were road traffic accidents (44.47%), fall from height (29.69%), heavy weight bearing (14.58%) and assault with gunshot (07.29%). Paraparesis was most frequent (51.05%) clinical presentation followed by quadriparesis (45.83%). Significant number of patients (83.33%) required operative treatment (p<0.05) and 09.89% were managed conservatively. Mortality rate (03.64%) was insignificant (p>0.05%) and 03.12% patient refused to take treatment. Of these patients, 77.01 % had shown neurological improvement of at least one grade according to ASIA Score. Conclusion: Wide varieties of patients are encountered and managed varying from conservative to surgery. Carefully selected treatment provides the utmost outcome and reduces mortality.